Internacionalização do saber jurídico e redes profissionais locais: um estudo sobre justiça restaurativa em São Carlos-SP e São Caetano do Sul-SP - Tonche, Juliana (2010)
I analyze the articulation process existing between the juridical knowledge internationalization, represented here by restorative justice, and local professional networks in two cities from the state of São Paulo: São Carlos and São Caetano do Sul. In the first city it was observed a interest decay in restorative justice with a local configuration of disputes towards the minor with problems against the law. Then, the second city is constituted as one of the three areas in this country in which was established a pilot program of mediation in the shapes of the kind of informal resolution of conflicts indicated here. Based on a bibliography on sociology of professions, it is discussed how this proposal, with a more political content, has been treated more specifically in the field of law professions, assuming that these professions, unique in their historical tradition and strong connection with the State, have taken the knowledge neutrality and strong delimitation with political field as the best strategy for the construction of their autonomy.